2014
DOI: 10.1039/c3fo60631g
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the satiating properties of a nutraceutical product containing Garcinia cambogia and Ascophyllum nodosum extracts in healthy volunteers

Abstract: A nutraceutical product composed of a combination of Garcinia cambogia, l-carnitine and a seaweed extract of Ascophyllum nodosum has been recently developed. The aim of the present study was to characterize its effects on subjective satiety sensations and food preferences in healthy volunteers. In a crossover design, 28 subjects (21 females and 7 males, aged 31 ± 5, BMI 22.6 ± 1.7) were randomly assigned to receive the active treatment (LIS) or placebo (PL) over one week. At the end of each treatment period, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Furthermore, this study revealed a significant reduction in TC, total TG, AI, AC, CRR, and blood pressure lowering effect significantly due to the treatment with G. cambogia that led to a reduction in the visceral and subcutaneous fat accumulations regardless of gender effect [ 29 ]. This potential effect of G. cambogia was due to the effects of the active ingredient, HCA that inhibits lipogenesis and reduction in LDL levels that causing amelioration in vascular and visceral functions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study revealed a significant reduction in TC, total TG, AI, AC, CRR, and blood pressure lowering effect significantly due to the treatment with G. cambogia that led to a reduction in the visceral and subcutaneous fat accumulations regardless of gender effect [ 29 ]. This potential effect of G. cambogia was due to the effects of the active ingredient, HCA that inhibits lipogenesis and reduction in LDL levels that causing amelioration in vascular and visceral functions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to placebo, active treatment resulted in significantly increased satiety and fullness ratings and reduced subjective hunger sensations. Concomitantly, authors reported that the active treatment was also associated with a reduction in implicit wanting and explicit liking for savoury foods and a reduction in the preference for high fat foods in both study groups [52].…”
Section: Impacts On Appetitementioning
confidence: 87%
“…Besides, a significant decrease in appetite and increase in hunger was seen by P. vulgaris (with dose of 100 mg/day; Spadafranca et al, ), C. fimbriata (with dose of 1,000 mg/day; Kuriyan et al, ), spinach (with dose of 5,000 mg/day; Rebello et al, , Stenblom, Egecioglu, Landin‐olsson, & Erlanson‐albertsson, ), flaxseed (with dose of 2,500 mg/day; Ibrugger, Kristensen, Mikkelsen, & Astrup, ), fenugreek (with dose of 8,000 mg/day; Mathern, Raatz, Thomas, & Slavin, ), G. cambogia (with dose of 1,000 mg/day; Mayer et al, , Preuss et al, ), green coffee (Roshan, Nikpayam, Sedaghat, & Sohrab, ), and the combination simplicifolia , asiatica , Taraxacum officinale , Cynara Scolymus , Paullina Sorbilis , Alga Klamath (Rondanelli, Klersy, Iadarola, Monteferrario, & Opizzi, ), and a combination of G. cambogia and Amorphophallus konjac (Vasques et al, ; Figure ). Some other articles have shown that Gundelia tournefortii (Hajizadeh‐Sharafabad, Alizadeh, Mohammadzadeh, Alizadeh‐Salteh, & Kheirouri, ), Coleus forskohlii (Loftus et al, ), N. sativa (Mahdavi et al, ), Garcinia atroviridis (Roongpisuthipong, Kantawan, & Roongpisuthipong, ), C. fimbriata (Kuriyan et al, ), a combination of ephedra and caffeine (Hackman et al, ) as well as a combination of walnut and flaxseed (Wu et al, ) significantly reduces energy intake (Figure ).…”
Section: Discussionmentioning
confidence: 99%